Short-, mid-, and long-term complications after multisystem inflammatory syndrome in children over a 24-month follow-up period in a hospital in Lima-Peru, 2020–2022 - Alvarado-Gamarra, Giancarlo; Estupiñan-Vigil, Matilde; Garcés-Ghilardi, Raquel; Domínguez-Rojas, Jesús; del Águila, Olguita; Alcalá-Marcos, Katherine; Márquez Llanos, Rafael; Ecker, Lucie; Celis, Carlos R.; Alva-Diaz, Carlos; Lanata, Claudio F. (Frontiers in Pediatrics, 2023)
Objective: To determine the short-, mid-and long-term complications after MIS-C over a 24-month follow-up period in a hospital in Lima, Peru, 2020-2022, and to explore differences according to the immunomodulatory treatment received and type of SARS-CoV-2 virus circulating. short-term, midterm and long-term complications of multisystem inflammatory syndrome in children (MIS-C) according to immunomodulatory treatment and type of SARS-CoV-2 epidemic wave in a hospital in Lima-Peru, 2020-2022. Methods: Ambispective 24-month follow-up study in children <14 years of age diagnosed with diagnosis of MIS-C at the Hospital Nacional Edgardo Rebagliati Martins (HNERM), until a 24-month follow-up. Results: Sixty-two children were admitted with MIS-C. The most common short-term complications and serious events were intensive care unit (ICU) admission, invasive mechanical ventilation (IMV) due to respiratory failure, and shock; predominantly during the second pandemic wave (lambda predominance) and in children that received intravenous immunoglobulin (IVIG) plus a corticosteroid. Macrophage activation syndrome (MAS) was more frequent during the third wave (Omicron predominance). Longer hospitalization time was required in those who didn'tnot receivinge immunomodulators. Two patients died during the first wave due to MIS-C. During prospective follow-up (median of 24 months; IQR: 16.7 to 24), only 46.7% patients were followed for >18 to 24 months. Of the total, seven (11.3%) patients were identified with some sequelae on discharge. Among the 43 remaining children, sequelae persisted in five (11.6%) cases (neurological, hematological and skin problems). Six patients (13.9%) presented new onset-disease (hematologic, respiratory, neurological and psychiatric disorders).